Structure-guided design of a truncated heterobivalent chemical probe degrader of IRE1α - Zerfas, Breanna L; Liu, Yingpeng; Che, Jianwei; Donovan, Katherine A; Hatcher, John M; Huerta, Fidel; Metivier, Rebecca J; Nowak, Rados aw P; Ragosta, Leah; Tsang, Tiffany; Fischer, Eric S; Jones, Lyn H (RSC medicinal chemistry, 2025)
IRE1α is an ER protein involved in the unfolded protein response (UPR) and dysregulation of the ER stress pathway has been implicated in several diseases. Inhibitors of the cytoplasmic endonuclease or kinase domains of the enzyme have limited utility and targeted degradation would address additional scaffolding functions of the protein. Here, we describe the design and development of IRE1α proteolysis targeting chimeras (PROTACs) based on a lysine-reactive salicylaldehyde RNase inhibitor, and present the structure-activity relationships (SARs) that delivered the first highly selective degraders of a native ER-membrane associated protein. Medicinal chemistry optimization exploited ternary complex computational modelling to inform design, HiBiT-SpyTag IRE1α degradation and NanoBRET cereblon occupancy cell-based assays to generate SARs, and mass spectrometry-based proteomics to assess broad selectivity in an unbiased manner. Merging IRE1α and CRBN ligand chemotypes provided the truncated chimera CPD-2828 with physicochemical properties more akin to an oral molecular glue degrader than a traditional PROTAC. The first degrader of an ER-resident protein (IRE1α) is described with properties more akin to a molecular glue than a traditional PROTAC, thus challenging the dogma of categorizing degrader modalities based on their physicochemical features.